Identification of Trypanosoma brucei components involved in trypanolysis by normal human serum. Issue 3 (25th September 2014) - Lecordier, Laurence; Uzureau, Pierrick; Tebabi, Patricia; Pérez‐Morga, David; Nolan, Derek; Schumann Burkard, Gabriela; Roditi, Isabel; Pays, Etienne
Summary Normal human serum (NHS) confers human resistance to infection by the parasite Trypanosoma brucei owing to the trypanolytic activity of apolipoprotein L1 (APOL1), present in two serum complexes termed Trypanolytic Factors (TLF‐1 and ‐2). In order to identify parasite components involved in the intracellular trafficking and activity of TLFs, an inducible RNA interference (RNAi) genomic DNA library constructed in bloodstream form T. brucei was subjected to RNAi induction and selection for resistant parasites under NHS conditions favouring either TLF‐1 or TLF‐2 uptake. While TLF‐1 conditions readily selected the haptoglobin‐haemoglobin (HP‐HB) surface receptor TbHpHbR as expected, given its known ability to bind TLF‐1, under TLF‐2 conditions no specific receptor for TLF‐2 was identified. Instead, the screen allowed the identification of five distinct factors expected to be involved in the assembly of the vacuolar proton pump V‐ATPase and consecutive endosomal acidification. These data confirm that lowering the pH during endocytosis is required for APOL1 toxic activity.